PENAPISAN KHAMIR SELULOLITIK DAN XILANOLITIK DALAM MENDUKUNG PEMBENTUKAN BIOETANOL - Rahayuni Bahati; Suhartono Suhartono; I Made Sudiana (Program Studi Kimia Universitas Negeri Jakarta, 2013)
Awareness of the impact of fossil fuels and limited fuel stocks has encourage to find alternative energy sources such as bioethanol. In this research biomass lignocelluloses (cellulose and xylan) used by yeast to produce bioethanol through hydrolysis and fermentation. The objective of this research is to discover yeast isolates that have cellulolitic and xylanolitic ability and its potential to form bioethanol. 43 yeast isolates isolated form leaf, litter, and soil at Mekongga and Papilia Sulawesi, which are collections of LIPI Microbiology Culture Collection. Selection of yeast isolates usin